The Impact of a Break-Through Rule on European Firms - Morten Bennedsen; Kasper Nielsen (Copenhagen Business School (CBS), Department of Economics, 2002)
We analyze the impact of a 75 pct. Break-Through rule on 1,035 European firms with dual class shares. In 3-5 pct. of the firms the controlling owners incur a direct loss of control, whereas in additional 11-17 pct. of the firms the controlling owners are likely to incur a control loss. Firms in Germany, Italy and the Scandinavian countries are more likely to incur a control loss. We continue to estimate the restrictions that the Break-Through rule puts on these firms' ability to issue new shares to outsiders without changing the control structure. We conclude that a significant number of the firms with dual class shares in the European Union will be affected by a 75 pct. Break- Through rule.
hdl:10398/7514
Keywords: G30; G32; G34; G38; 330; Break-Through rule; Dual class shares; Corporate control; Takeovers and Voting rights